Blockchain Technology – Current Status, Challenges and Perspectives in Tax and Customs Law - Hrabčák, Ladislav; Stojáková, Monika (Public Governance, Administration and Finances Law Review, 2020)
One of the hallmarks of the 21st century society is rapid technological progress. It must be addressed by national legal systems, which is another theme discussed in this article. Blockchain technology is one of the most current issues, not only in information technology, but also in law. This paper aims to assess the current legal situation and to reflect on the challenges and perspectives that are undoubtedly related to Blockchain, as it focuses on tax and customs law. Whether Blockchain is capable of contributing to more efficient tax and customs collection is a fundamental hypothesis that we will attempt to confirm or refute.